Construção de um veículo autônomo para aplicação de produtos fitossanitário - Rezende, Pablo Franco de (2017)
The competition between cultures of agricultural interest and invasive plants is a problem that lasts several years, therefore, the industries of agricultural pesticides are the most benefit from this gap in agriculture. But the effects of these pesticides are not yet fully known. Based on this, the goals of this work are to build and evaluate an unmanned ground vehicle, spraying system with fractioned dose; study of photoelectric optical sensor use HC-SR501 PIR, real-time detection of invasive plants in two different surfaces (surface red Latosol, light surface), with five different infestation indices for both; develop a computational program in C language for a lowcost electronics that scan the information captured by the sensor and reverse flow control. Construction and study were conducted at the Federal University of Mato Grosso, câmpus of Rondonópolis, the evaluations were carried out in the experimental area of Agricultural and environmental engineering course, on various conditions (temperature, relative humidity and dust), the split spray system work properly the activity to which it was designed; the VTA proved to be a suitable structure to the study of sensors; the HC-SR501 sensor PIR detected the infrared reflectance of different leaf areas which was submitted, but without reliable results, being the clear surface presented more sense failure.